Application of Starch and Starch-Based Products in Food Industry - Mohamad Yazid, Nurulain Syuhada; Abdullah, Norazlin; Muhammad, Norhayati; Matias-Peralta, Hazel Monica (Journal of Science and Technology, 2018)
Starch is an edible polymer derived from plant basis. It is commonly used in food industry as it offers good stabilising effect. Moreover, starch can be easily modified either physically or chemically making it a very versatile source. For instance, its capability to be easily modified and coming from low cost source making starch as one of the most important ingredient in food preparation. There are currently varieties of commercially modified starch available in Malaysian market. For example, potato, corn, wheat and tapioca starch are presently on the top list. However, there are also numbers of unexplored native starch for example from fruits processing waste. Besides, these fruit by-products are considered as underutilised source of starch. Although there are few existing reported studies on starch extracted from fruits seed and other waste products, more new sources are believed to be explored in future according to particular starch-based products industries and demands. Therefore, this review discusses current starch based-products developments and application of unconventional starch in food industry.